Online shopping in Malaysia: legal protection for e-consumers - Amin, Naemah; Mohd Nor, Roshazlizawati (IISTE, 2013)
The rapid growth in e-commerce witnesses the emergence of a new group of consumers known as e-consumers. This new group of consumers is increasing in number over the years as online shopping become a trend and a manifestation of the modern life style. However a distance and complex nature of online shopping has led to some new problems and challenges pertaining to consumer protection. One of the perennial problems that needs considerable attention is the adequacy of the existing legislation in Malaysia to meet the basic needs of online consumers. Even though the Consumer Protection Act 1999 (CPA) was amended in 2007 in order to protect the interests of e-consumers, the question remains as to how far the CPA and other existing legislation, namely the Contracts Act 1950, Sale of Goods Act 1957, Direct Sales and Anti-Pyramid Scheme Act 1993 and Electronics Commerce Act 2006 can protect e-consumers in sale of goods contracts. Therefore, this paper is tasked to generally analyze the existing Malaysian law on sale of goods and to determine the extent to which those laws are adequate in providing protection and preserving the interests of e-consumers in order to overcome their anxieties as well as building up their confidence in purchasing goods online.